2012
DOI: 10.4236/jmf.2012.21013
|View full text |Cite
|
Sign up to set email alerts
|

A Skewness-Adjusted Binomial Model for Pricing Futures Options—The Importance of the Mean and Carrying-Cost Parameters

Abstract: In this paper, we extend the Johnson, Pawlukiwicz, and Mehta [1] skewness-adjusted binomial model to the pricing of futures options and examine in some detail the asymptotic properties of the skewness model as it applies to futures and spot options. The resulting skewness-adjusted futures options model shows that for a large number of subperiods, the price of futures options depends not only on the volatility and mean but also on the risk-free rate, asset-yield, and other carrying-cost parameters when skewness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Most option models assume a symmetric distribution for the asset returns, but Johnson, Pawlukiewicz, and Mehta (1997) and Johnson, Sen, and Balyeat (2012) derive a binomial option pricing model that allows for a skewed distribution. Based on their more complex model, the effect of skewness on an option's value can be assessed by considering the probability that a drug is a success, q:…”
Section: A Real Options Model Of Drug Randd Investment When Benefits mentioning
confidence: 99%
“…Most option models assume a symmetric distribution for the asset returns, but Johnson, Pawlukiewicz, and Mehta (1997) and Johnson, Sen, and Balyeat (2012) derive a binomial option pricing model that allows for a skewed distribution. Based on their more complex model, the effect of skewness on an option's value can be assessed by considering the probability that a drug is a success, q:…”
Section: A Real Options Model Of Drug Randd Investment When Benefits mentioning
confidence: 99%
“…Skewness plays an important role in statistical analyses in almost all disciplines, and especially in finance. Johnson, Sen and Balyeat [7] applied a skewness adjusted binomial model to futures options pricing and derived the asymptotic skewness model properties. Their results showed that the futures options price, in the presence of skewness, depends not only on mean and standard deviation DOI: 10.4236/ojs.2019.95039 602 Open Journal of Statistics (sd), but other parameters as well.…”
Section: Introductionmentioning
confidence: 99%
“…respectively. This is a standard procedure (Ingersoll (1987)) and is widely applied as similar expressions can be found in Johnson et al (1997) for non-standardized skewness, Barberis and Xiong (2009), Ebert and Strack (2009) and Johnson et al (2012). The corresponding upside probabilitiesp t are derived from our estimates of Γ t , where we usep t as the remaining degree of freedom to implement the connection to the skewness of the return distribution, such thatp t =…”
mentioning
confidence: 99%